Respostas
respondido por:
1
Explicação passo-a-passo:
fatorando o 27 = 3³
se as bases são iguais, os expoentes são iguais
x² - x - 3 = 3
x² - x - 3 - 3 = 0
x² - x - 6 = 0 (a = 1 ; b = -1 ; c = -6)
usando a fórmula quadrática, fica
x = -b ± √(b² - 4ac)
2a
x = - (-1) ± √((-1)² - 4 × 1 × (-6))
2 × 1
x = 1 ± √(1 + 24)
2
x = 1 ± √25
2
x = 1 ± 5
2
x₁ = 1 + 5 → x₁ = 6 → x₁ = 3
2 2
x₂ = 1 - 5 → x₂ = -4 → x₂ = -2
2 2
Resposta: x = 3 e x = -2
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás